New perspectives on the progression of pulmonary fibrosis: the cascade from aberrant microvascular endothelial cell activation to fibrosis - Zhou, Jie; Xia, Xiuwen; An, Xing; Liu, Danping; Zhao, Hongyi; Sun, Zengtao; Li, Weihong; Huang, Qingsong (Frontiers in Medicine, 2025)
Traditional studies of pulmonary fibrosis (PF) have focused on alveolar epithelial cells injury and abnormal myofibroblast aggregation, but recent studies have revealed that imbalances in pulmonary capillary homeostasis also play pivotal roles in this disease. The pulmonary microvasculature, composed of aerocyte capillary (aCap) and general capillary (gCap) endothelial cells, forms the core structure of the alveolar-capillary membrane. It performs key roles in gas exchange and nutrient/metabolite transport, while modulating the trafficking of inflammatory factors and immune cells and regulating alveolar damage repair. Abnormal activation of pulmonary microvascular endothelial cells in pulmonary fibrosis, reprogramming of cellular metabolism, secretion of proinflammatory and profibrotic factors, and disruption of pulmonary capillary homeostasis, lead to abnormal remodeling of the pulmonary microvasculature and other pathological changes, promoting the deterioration of PF. Notably, maintaining and restoring normal pulmonary capillary homeostasis is beneficial for improving the local microenvironment of fibrotic lesions and attenuating pathological changes such as hypoxia. In this review, the pathological changes associated with pulmonary capillary homeostasis imbalance in PF are described. Therapeutic directions for restoring pulmonary capillary homeostasis are also proposed with the expectation that they will provide assistance in the treatment of PF.